2020
DOI: 10.1002/edm2.168
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations on endothelium‐dependent flow‐mediated vasodilation in adults with type 2 diabetes and nondiabetic adults with hypertension and/or dyslipidaemia who perform regular exercise

Abstract: Introduction Endothelium‐dependent flow‐mediated dilation (FMD) of the brachial artery often changes seasonally. We aimed to examine the association between the seasonal variation on FMD and regular exercise in adults with type 2 diabetes (T2D) and nondiabetic adults with hypertension and/or dyslipidaemia (non‐T2D). Methods This retrospective study included 14 T2D and 17 non‐T2D adults, who started to perform moderate‐intensity aerobic exercise for 30‐40 min/d at a hospital gym in 2006‐2010 and maintained exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…FMD values were lower in winter than those in the other seasons (33). Whether this variation depends on the initial values remains unknown; however, this should be considered in subsequent analyses.…”
Section: Discussionmentioning
confidence: 89%
“…FMD values were lower in winter than those in the other seasons (33). Whether this variation depends on the initial values remains unknown; however, this should be considered in subsequent analyses.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies that evaluated seasonal variation in FMD were performed without taking into account the individuals' PA (e.g., exercise habits) [23,61] (Figure 1). Seasonal variations in vascular function may be observed even if individuals perform exercises throughout the year, although the influence of total daily PA is unclear [93].…”
Section: Influence Of Pa On Seasonal Variations In Metabolic and Vascular Functionmentioning
confidence: 99%
“…A previous study on children (n = 116, 40% boys, mean age: 10.4 years for boys) showed that seasonal variations in the FMD value correlated with those in vigorous-intensity physical activity, although not in low-and moderate-intensity physical activities [73]; remarkably, when the authors analyzed the data according to sex differences, this correlation was only observed for boys. Another study on adults with type 2 diabetes, hypertension, and/or dyslipidemia (n = 31, 39% men, mean age: 66.3 years) showed that maintaining exercise habits by going to a gym could not diminish the deterioration of the FMD value and blood pressure during the winter, although it could suppress seasonal variations in some metabolic functions (e.g., blood lipid profiles) [74]. However, there is a lack of evidence regarding the association between seasonal variations in physical activity and vascular endothelial function for various age groups; naturally, it is unclear whether sex affects the association.…”
Section: Association Between Seasonal Variations In Physical Activity and Vascular Endothelial Functionmentioning
confidence: 99%